Massive open online course (mooc) based desa skill application - Supina Batubara; Teguh Wahyono; Abdul Khaliq; Yuli Ennisa Lubis (Institute of Computer Science (IOCS), 2023)
This research aims to build skills applications that can be used to collect skills data and improve the skills possessed by the community, while understanding concepts that can be done to improve digital community resource management and provide applications to analyze information exchange online. Sampling was carried out through intentional data collection techniques using questionnaires and tests. The Skill Village application is built using massive open online course (MOOC) technology, and complex problems are handled through complex computer simulation technology and massive open online course technology, a computer engineering education model that can adapt quickly. Implementing an online skills village information exchange application to support and improve the skills and management of community resources. Community resources that are well managed can reduce unemployment, so that the positive impact that is felt is an increase in people's income. Testing the Skill Village application was carried out using the -t test and gain test techniques, where the t test was used to test hypotheses and the gain test was used to determine the significant results of the community's professional level